0
$\begingroup$

Enderton claims that it is not hard to show that a deduction for $\{\forall x (Px \to Qx), \forall z P z\} \vdash Qc$ exists, and furthermore that it consists of only seven formulas. I was able to find such a deduction but considering instead the set of hypotheses $\Gamma = \{\forall x (Px \rightarrow Qx), \forall x P x\}$. Otherwise, getting $\forall x P x$ from $\forall z P z$ takes me about 6 formulas by mimicking the proof of the Generalization Theorem. Here's a depiction of the 7-formula deduction I arrived at:

  1. $\forall x(Px \to Qx) \to (\forall x Px \to \forall x Qx)$. In axiom group 3.
  2. $\forall x (Px \to Qx)$. In $\Gamma$.
  3. $\forall x Px \to \forall x Qx$. 1,2; Modus Ponens.
  4. $\forall x Px$. In $\Gamma$.
  5. $\forall x Qx$. 3, 4; Modus Ponens.
  6. $\forall x Qx \to Qx_{c}^{x}$. In axiom group 2 (substitution).
  7. $Qc$. 5,6; Modus Ponens.

Could anybody confirm that what Enderton claims cannot be done in 7 formulas/steps, or provide such a deduction?

$\endgroup$
0
$\begingroup$

A different derivation ...

1) $∀x(Px → Qx)$ --- premise

2) $∀zPz$ --- premise

3) $∀x(Px → Qx) \to (Pc → Qc)$ --- Axiom 2

4) $∀zPz \to Pc$ --- Axiom 2

5) $Pc → Qc$ --- 1) and 3) by MP

6) $Pc$ --- 2) and 4) by MP

7) $Qc$ --- 5) and 6) by MP.

$\endgroup$
  • $\begingroup$ Gratitude. I should know better than to doubt an author so easily! $\endgroup$ – MuchToLearn Feb 9 at 21:47

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.